2007
DOI: 10.1128/aem.01686-06
|View full text |Cite
|
Sign up to set email alerts
|

Operon Prediction for Sequenced Bacterial Genomes without Experimental Information

Abstract: Various computational approaches have been proposed for operon prediction, but most algorithms rely on experimental or functional data that are only available for a small subset of sequenced genomes. In this study, we explored the possibility of using phylogenetic information to aid in operon prediction, and we constructed a Bayesian hidden Markov model that incorporates comparative genomic data with traditional predictors, such as intergenic distances. The prediction algorithm performs as well as the best pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
(50 reference statements)
2
35
0
Order By: Relevance
“…These results revealed, as suggested by the bioinformatics analyses, that coaX is the first gene in a tricistronic operon. This operon assignment is also consistent with the results obtained with the operon prediction algorithm developed by Bergman et al (5).…”
supporting
confidence: 81%
“…These results revealed, as suggested by the bioinformatics analyses, that coaX is the first gene in a tricistronic operon. This operon assignment is also consistent with the results obtained with the operon prediction algorithm developed by Bergman et al (5).…”
supporting
confidence: 81%
“…The homologs in B. anthracis maintain this gene order (GBAA2368 to -2372), but in B. anthracis, three downstream genes (GBAA2373, -2374, and -2375) that are not present in the B. subtilis dhb region are also overexpressed after paraquat treatment at levels roughly equivalent to those observed for GBAA2368 to -2372 (Table 3, siderophore biosynthesis). Homologs of these three genes are often found near nonribosomal peptide synthesis operons in other bacteria (73), and the operon prediction algorithm described by Bergman et al (5) predicts that cotranscription of these three genes in B. anthracis is highly probable. End point RT-PCR probing for overlapping transcription products confirms that these genes are included in the B. anthracis bac transcriptional unit (data not shown), further highlighting differences between B. subtilis and B. anthracis.…”
Section: Vol 189 2007mentioning
confidence: 99%
“…One prominent group of genes overexpressed by the āŒ¬sodA1 mutant during logarithmic growth consists of GBAA1778, -1779, and -1780 (up-regulated 49-, 23-, and 31-fold, respectively). An operon prediction algorithm developed by Bergman et al (5) predicts that the first two genes are most certainly transcribed as one unit, whereas inclusion of the third gene is less certain. End point RT-PCR using primers designed to amplify overlapping gene regions showed that these three genes are, in fact, transcribed as one unit (data not shown).…”
Section: Vol 189 2007mentioning
confidence: 99%
“…Its genome sequence (29,30) contains 2125 ORFs. A universal feature of prokaryotic genomes is the organization of genes into operons, which form basic transcriptional units (31) and are important in functional genomics. Using a neural network, we predicted that 1460 ORFs in the P. furiosus genome are contained within 470 operons (32), 349 of which were validated using DNA microarray data (33,34).…”
mentioning
confidence: 99%